The role of self-regulated learning in literal comprehension among adult learners in private universities in Indonesia - Umi Tursini; Agus Sholeh; Nara Sari; Siti Mafulah (Journal of Research on English and Language Learning (J-REaLL), 2026)
There is a lack of empirical research on the role of self-regulated learning (SRL) in literal reading comprehension among adult learners, particularly in non-Western contexts such as Indonesia. Most previous studies have examined SRL in broader educational settings, leaving a limited understanding of how self-regulation supports specific literacy skills, especially literal comprehension. This study, therefore, investigates the effect of SRL on the literal reading performance of adult learners in a private university in Indonesia and examines how different levels of SRL influence learning outcomes after instruction. This study employed a quasi-experimental design involving 48 adult learners. Participants were categorized into high-SRL and low-SRL groups using the self-regulation questionnaire (SRQ). Data were collected through pre-test and post-test assessments of literal reading comprehension. Descriptive statistics were used to examine changes in literacy scores, while inferential analyses, including paired t-tests, independent t-tests, and correlation analysis, were conducted to determine the significance of differences between the two groups and the relationship between variables. The findings revealed that the mean score increased from 68.50 in the pre-test to 76.83 in the post-test, indicating an improvement of 8.33 points after instruction. A moderate positive correlation (r = 0.655) was also identified between pre-test and post-test scores while controlling for SRL, suggesting that learners with higher SRL tended to achieve better reading performance. However, the relative influence of SRL on post-instruction performance appeared slightly reduced, indicating that instructional support may help lower-SRL learners narrow the performance gap.